Inhibitor of differentiation 1 transcription factor promotes metabolic reprogramming in hepatocellular carcinoma cells. Issue 1 (1st September 2015) - Sharma, Bal Krishan; Kolhe, Ravindra; Black, Stephen M.; Keller, Jonathan R.; Mivechi, Nahid F.; Satyanarayana, Ande
ABSTRACT: Reprograming of metabolism is one of the central hallmarks of cancer. The majority of cancer cells depend on high rates of glycolysis and glutaminolysis for their growth and survival. A number of oncogenes and tumor suppressors have been connected to the regulation of altered glucose and glutamine metabolism in cancer cells. For example, the oncogene c‐Myc plays vital roles in cancer cell metabolic adaptation by directly regulating various genes that participate in aerobic glycolysis and glutaminolysis. Inhibitor of differentiation 1 (Id1) is a helix‐loop‐helix transcription factor that plays important roles in cell proliferation, differentiation, and cell fate determination. Overexpression of Id1 causes intestinal adenomas and thymic lymphomas in mice, suggesting that Id1 could function as an oncogene. Despite it being an oncogene, whether Id1 plays any prominent role in cancer cell metabolic reprograming is unknown. Here, we demonstrate that Id1 is strongly expressed in human and mouse liver tumors and in hepatocellular carcinoma (HCC) cell lines, whereas its expression is very low or undetectable in normal liver tissues. In HCC cells, Id1 expression is regulated by the MAPK/ERK pathway at the transcriptional level. Knockdown of Id1 suppressed aerobic glycolysis and glutaminolysis, suggesting that Id1 promotes a metabolic shift toward aerobic glycolysis. At the molecular level, Id1 mediates its metabolic effects by regulating the expression levels of c‐Myc. Knockdown of Id1 resulted in down‐regulation (~75%) of c‐Myc, whereas overexpression of Id1 strongly induced (3‐fold) c‐Myc levels. Interestingly, knockdown of c‐Myc resulted in down‐regulation (~60%) of Id1, suggesting a positive feedback‐loop regulatory mechanism between Id1 and c‐Myc. Under anaerobic conditions, both Id1 and c‐Myc are down‐regulated (50‐70%), and overexpression of oxygen‐insensitive hypoxia‐inducible factor 1α (Hif1α) or its downstream target Mxi1 resulted in a significant reduction of c‐Myc and Id1 (~70%), suggesting that Hif1α suppresses Id1 and c‐Myc under anaerobic conditions via Mxi1. Together, our findings indicate a prominent novel role for Id1 in liver cancer cell metabolic adaptation.—Sharma, B. K., Kolhe, R., Black, S. M., Keller, J. R., Mivechi, N. F., Satyanarayana, A. Inhibitor of differentiation 1 transcription factor promotes metabolic reprogramming in hepatocellular carcinoma cells. FASEB J. 30, 262‐275 (2016). www.fasebj.org